Considering Dawam Raharjo as the Foundation of Sharia Digital Business Ethics - Azzumi, Aufa Rizka; Aziz, Jamal Abdul (Program Studi Perbankan Syariah Universitas Pahlawan Tuanku Tambusai, 2023)
Purpose - This research aims to investigate the application of ethics in Sharia digital business and its potential impact on consumer trust and satisfaction in the context of Islamic fintech. The rapid expansion of Sharia fintech has led to the need for strong business ethics to guide and ensure the provision of quality services in the industry. Islamic business ethics, based on Sharia principles, play a crucial role in maintaining the continuity of Sharia business and promoting healthy competition. Additionally, the study explores the potential of Sharia digital business ethics in empowering society and supporting social empowerment initiatives within the framework of Islamic economics. Method – The research methodology employed in this study is qualitative content analysis, utilizing the works of Dawam Rahardjo as primary data sources. The data collection involves the analysis of written documents, including books authored by Rahardjo. The analysis focuses on identifying the compatibility and relevance between the draft ethical principles proposed by Rahardjo and the applied values in Sharia digital business. The life history approach is also employed to gain insights into Rahardjo's perspectives on business ethics. Result– The literature review examines the perspectives of Dawam Rahardjo, a prominent figure in Islamic economics, on Islamic business ethics. Rahardjo emphasizes the importance of fairness, transparency, responsibility, and accountability in business operations. The concept of